Percutaneous Endoscopic Management for Oriental Cholangiohepatitis: A Case Report and a Brief Review of the Literature - Khalil Aloreidi; Prince Sethi; Terry Yeager; Muslim Atiq (Case Reports in Gastrointestinal Medicine)
Oriental cholangiohepatitis (OCH) is a disease characterized by intrabiliary pigment stone formation, resulting in recurrent bouts of cholangitis. OCH is found mostly in Southeast Asia but it is occasionally recognized in Western societies. OCH etiology is largely unknown. We report our experience with a patient who presented with acute cholecystitis. Following laparoscopic cholecystectomy, she developed acute cholangitis due to multiple biliary tree stones. She underwent ERCP to clear the stones from common bile duct. For the intrahepatic stones, she underwent novel hybrid percutaneous endoscopic technique. The procedure resulted in complete clearance of biliary tree stones and resolution of her symptoms. The aim of this case is to increase awareness of this disease when patients from endemic areas present with biliary stones.